Pengaruh Risk Management Disclosure Terhadap Siklus Penjualan Dan Piutang Usaha Pada Perusahaan F&B Yang Terdaftar Di Bursa Efek Indonesia - Hardiyanti Dahlan; Mustianti; Nur Afika; Ririn Amelia Juliasti; Rahmawati Nur Siduppa (Program Studi Akuntansi Fakultas Ekonomi UMN AL Washliyah, 2025)
This study aims to analyze the effect of Enterprise Risk Management (ERM) disclosure based on the COSO framework on the effectiveness of the sales cycle and accounts receivable collection, which is measured through Days Sales Outstanding (DSO), Receivable Turnover (RT), and Bad Debt Ratio (BDR). The research uses a quantitative approach with data from the annual reports of six Food and Beverage (F&B) companies listed on the Indonesia Stock Exchange (IDX) for the 2020-2024 period. Data were analyzed using normality, linearity, simple linear regression, T-test, and determination coefficients with the help of SPSS software. The results showed that ERM disclosure had a positive and significant effect on DSO and RT, but did not have a significant effect on BDR. The value of the determination coefficient (R²) in DSO and RT was 9.5%, indicating that ERM was able to explain the variation of the two variables, while 90.5% was influenced by other factors. Overall, the results of the study strengthen the hypothesis that the application of ERM makes a positive contribution to improving the effectiveness of sales cycle management and accounts receivable.